2019
DOI: 10.1161/circulationaha.119.040366
|View full text |Cite
|
Sign up to set email alerts
|

Severe Cardiac Dysfunction and Death Caused by Arrhythmogenic Right Ventricular Cardiomyopathy Type 5 Are Improved by Inhibition of Glycogen Synthase Kinase-3β

Abstract: Supplemental Digital Content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
84
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(90 citation statements)
references
References 42 publications
4
84
2
Order By: Relevance
“…Arrhythmogenic right ventricular cardiomyopathy (ARVC) is a severe disease featured by an extensive fibrotic replacement. In animal models that recapitulate human ARVC, the cardiac fibrotic response was associated with an upregulation of Lox [83,84]. Finally, a strong induction of LOX was identified as the underlying cause of the restrictive cardiomyopathy evoked by a sustained running in SHR rats.…”
Section: Lox In Other Pathophysiological Settings Leading To Cardiac mentioning
confidence: 96%
“…Arrhythmogenic right ventricular cardiomyopathy (ARVC) is a severe disease featured by an extensive fibrotic replacement. In animal models that recapitulate human ARVC, the cardiac fibrotic response was associated with an upregulation of Lox [83,84]. Finally, a strong induction of LOX was identified as the underlying cause of the restrictive cardiomyopathy evoked by a sustained running in SHR rats.…”
Section: Lox In Other Pathophysiological Settings Leading To Cardiac mentioning
confidence: 96%
“…A mouse model of ARVC subtype 5 expressing a mutated form of the non-desmosomal gene TMEM43 showed cardiomyocyte death and severe fibrofatty replacement. AKT was found inhibited, leading to GSK-3β activation and consequent inhibition of β-catenin activity in this mouse model [ 23 ]. Furthermore, the pathogenic role of inhibition of Wnt signaling in ACM has been shown in an ACM transgenic mouse model with cardiomyocyte-specific overexpression of a FLAG-tagged human desmoglein-2 with the Q558* nonsense mutation [ 20 ] and in a zebrafish model of DSP deficiency [ 21 ].…”
Section: Molecular Pathogenic Pathwaysmentioning
confidence: 99%
“…Several molecular and cellular mechanisms have been proposed to explain the pathogenesis of ACM. It has been shown that the presence of the ACM causal mutations induce activation of the Hippo signaling and inhibition of the Wnt signaling and activation of transforming growth factor beta (TGFβ) signaling [ 1 , 2 , 17 , 18 , 19 , 20 , 21 , 22 , 23 ]. Recent studies suggest electric instability in early stages of ACM may be the consequence of dysregulation of ion channels and Ca 2+ signaling machinery, not only as direct effect of causal mutations located in genes encoding components of the Ca 2+ homeostasis, but also as consequence of mutations in desmosomal genes [ 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…The code for the simulations and the subsequent analysis of the data was conducted in Igor Pro. Electroporator Enhancer (22 pmol/each) were electroporated, and cells were recovered and split into p100 dishes as described (70). After 7-10 days, colonies were picked up and split into p96 and p24 well plates for screening and maintenance respectively.…”
Section: Monte Carlo Simulationsmentioning
confidence: 99%
“…One proved to be homozygous and another one heterozygous for the desired mutation. For cardiac differentiation, WT and TTN Cys3575Ser -hiPSC lines were expanded and dissociated into single cells as described (70). Briefly cells were seeded at a density of 1-1.2x10 6 cells per well in Essential E8 medium supplemented with 10 µM ROCK inhibitor.…”
Section: Monte Carlo Simulationsmentioning
confidence: 99%